Proyecto de creación de una empresa con el servicio de supermercado electrónico en la ciudad de Guayaquil. - Alvear, Ligia Leonor (2009)
The study of this project is based on determining the feasibility it gives on the creation of a company that offers the service electronic supermarket in Guayaquil city: for that reason is necessary have clear objectives of the project, they will be key for the development of our project . The description of the company, mission, vision and strategies of the company will be good to determine the type of business that will undertake. The study of offer, study of demand and study of market prices will help to determine the current market situation and if it is feasible the income gives for this type of business. The technical study, all the cost that will be required to carry out the business like the manpower, machineries, vehicles, furnitures, cost of constitution, among others; they will allow to elaborate the cash flow of the company and the projection to 5 years, that will determined if the project is profitable or no, the Present Value (NPV) and internal rate of return (IRR) will be analyzed